Paul Ricoeur diszdoktori avatás - Part 2
Continuation of the audio recording of the event held on Sunday, March 9, 2003 when the CEU Senate offered the honorary doctorate to philosopher Paul Ricoeur. Contains the end of Prof. Sorin Antohi’s presentation.